Mixed laryngopyocele presenting as acute airway obstruction: case report - Ribeiro, Susana (2010)
A laryngocele is an abnormal dilatation of the laryngeal saccule which communicates with the laryngeal lumen. It may be congenital or acquired; the acquired type has a multifactorial ethiopathogenesis and may be related to the increase in the intralaryngeal pressure. Typically it is found in caucasian male individuals and in their fifth or sixth decades of life; it is more frequently unilateral and combined or mixed type. Usually it develops slowly; however it may present as acute airway obstruction requiring urgent intubation or tracheotomy, as in the case of infection with the formation of a laryngopyocele. We report a case of a 71-year-old female patient, who sells flowers in a street, admitted in the Hospital de São José- Urgency Room with a history of odynophagia and dysphonia for one month and a half and that after being medicated with a new antibiotic develops an allergic reaction in need of Otorhinolaryngology care. The subsequent investigation revealed a mixed laryngopyocele. The laryngocele is a rare pathology and very few present as airway obstruction. It becomes infected in only 8% of the cases which makes this case report particularly rare. However we consider important to have this pathology in mind in the differential diagnosis of acute airway obstruction.